Quantifying impacts of oil palm expansion on Colombia's threatened biodiversity. (August 2018) - Ocampo-Peñuela, Natalia; Garcia-Ulloa, John; Ghazoul, Jaboury; Etter, Andres
Abstract: Large-scale conversion of forest to oil palm has precipitated severe environmental impacts in the lowlands of Malaysia and Indonesia. It is a major conservation priority to ensure that projected expansion of oil palm in Africa and Latin America does not lead to analogous environmental devastation in these mega-diverse places. In an effort to minimize negative impacts from a species conservation perspective, we present a framework for spatial planning that accommodates inevitable oil palm expansion into regions of high biodiversity. Using megadiverse Colombia as an example, we investigated current and projected impacts of oil palm on threatened vertebrates (birds, mammals, and amphibians). We highlight a few areas where expansion would be detrimental to threatened fauna and should be avoided, but generally, there is minimal overlap between suitable areas for oil palm production and threatened vertebrate distributions. Our analysis demonstrates that there is room for oil palm to expand in Colombia without incurring severe conservation risks for threatened vertebrates, so long as it avoids a few high-priority areas such as la Serranía de la Macarena, the Andes-Amazon transition, the Darién, and the Tumaco forests. By applying this approach to other countries facing imminent oil palm expansion, it may be possible to meet a growing commodity demand without severely exacerbating the biodiversity crisis. Highlights: Oil palm could expand at low conservation cost in Colombia. Overlap of threatened biodiversity and at risk ecosystems with current and projected oil palm plantations is minimal and spatially clustered. Establishment of oil palm plantations on pastures would be best for biodiversity. Areas with high concentrations of threatened biodiversity and in ecosystems at risk should be avoided when expanding oil palm. Spatial planning framework for planning low-conservation cost oil palm could be used in other tropical countries.